Pengaruh Motivasi Ekstrinsik & Motivasi Intrinsik Terhadap Prestasi Kerja Karyawan: Gender Sebagai Variabel Kontrol: Studi Pada PT. Pangan Sari Utama Kec. Hu'u Kab. Prov. Dompu Nusa Tenggara Barat - Apriliana, Nofita; Subiyanto , Didik; Septyarini, Epsilandri (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
The aim of this research is to analyze the influence of extrinsic motivation and intrinsic motivation on employee work performance: gender as a control variable. This research uses a quantitative method using a questionnaire with a sample size of 58 respondents or employees. The research results show that Extrinsic Motivation has a positive and significant influence on Intrinsic Motivation, Intrinsic Motivation has an influence on Job Performance, and Extrinsic Motivation has no influence on job performance. Keywords: Extrinsic Motivation, Intrinsic Motivation, Job Performance, Gender